Lymphedema A Concise Compendium of Theory and Practice (Springer International Publishing, 2018)
The second edition of this book serves as a central source of theoretical and practical knowledge to optimize the evaluation and treatment of patients with lymphedema. The book covers all aspects of the disease from anatomical and histological features to diagnosis as well as physical/medical and surgical management of the disease. Updated from the first edition to reflect the substantial progress in diagnostics, medical care and surgical intervention for this patient population, this volume has been reorganized to meet today's practice requirements. It addresses the challenges faced by clinicians in the management of chronic lymphedema enabling them to meet the medical needs of this large patient community. Edited by world leaders in Vascular Medicine and Surgery, this comprehensive volume provides clear, concise background and recommendations in an easy-to-use format. It is a valuable reference tool for clinical practitioners (physicians/nurse practitioners/technicians) who wish to deliver state-of-the-art health care to their patients with lymphatic and venous disorders.